Edukasi Pemberian Imunisasi Dasar Lengkap Pada Bayi dan Balita Di Posyandu Cempaka - Amelia Dini Anggraini Silalahi; Joni Siagian; Hafsanah; Kurnia Wati; Novia Elida Yanti Gurning (Jurnal Pengabdian Keperawatan Dan Kesehatan Holistik, 2025)
Vaccination has the ability to increase body immunity and fight infectious diseases. The health of the Indonesian people is decreasing due to the high infant mortality rate, and one effort to overcome this is through a vaccination program for infants and young children. However, this program still faces problems: opposition from parents. Some say that parents' reluctance to vaccinate is due to public misunderstanding about vaccines, lack of education, lack of knowledge about vaccines, some argue that whether or not they want to get immunized, they will still get a fever, and some say the reason is related to religion. The purpose of this intervention is to provide education to mothers who do not have access to basic health services. The method used is a lecture method with booklet media that provides direct information to mothers of infants and young children through open interaction. The results of the intervention obtained 81.0% of mothers had good knowledge and 19.0% of mothers had poor knowledge. The conclusion of this intervention is that most mothers know about vaccinations for their children, and it is hoped that good knowledge can help support good vaccinations for their children.